2018
DOI: 10.1159/000487053
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Retinal Imaging Biomarkers for Alzheimer’s Disease: A Pilot Study

Abstract: Purpose: To examine whether ultra-widefield (UWF) retinal imaging can identify biomarkers for Alzheimer’s disease (AD) and its progression. Methods: Images were taken using a UWF scanning laser ophthalmoscope (Optos P200C AF) to determine phenotypic variations in 59 patients with AD and 48 healthy controls at baseline (BL). All living participants were invited for a follow-up (FU) after 2 years and imaged again (if still able to participate). All participants had blood taken for genotyping at BL. Images were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 48 publications
9
62
0
Order By: Relevance
“…In this review, the outcomes of fractal analysis in neurodegeneration studies show a decreased FD in various degrees and etiologies of CI, including AD and vascular dementia, as opposed to cognitively normal controls. Despite rather small sample sizes, findings are consistent with effect sizes ranging from −0.018 (Csincsik et al, 2018) to −1.33 (Cabrera DeBuc et al, 2018). The findings in studies with stroke patients are less straightforward, probably due to the heterogeneity in both study design and methodological set-up.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In this review, the outcomes of fractal analysis in neurodegeneration studies show a decreased FD in various degrees and etiologies of CI, including AD and vascular dementia, as opposed to cognitively normal controls. Despite rather small sample sizes, findings are consistent with effect sizes ranging from −0.018 (Csincsik et al, 2018) to −1.33 (Cabrera DeBuc et al, 2018). The findings in studies with stroke patients are less straightforward, probably due to the heterogeneity in both study design and methodological set-up.…”
Section: Discussionsupporting
confidence: 67%
“…Three of these focused on CI, and even with differences in ROI, imaging device, vessel segmentation software, FD calculation method and software, all three confirmed a significant decrease of FD measures in CI (including dementia) (Cabrera DeBuc et al, 2018), mild CI (Jiang et al, 2018) and AD (Csincsik et al, 2018). After a follow-up period of 2 years, Csincsik et al reported that the significant difference in FD between AD and controls at baseline had become a trend (Csincsik et al, 2018), whereas Jiang et al described a trend of vascular density loss from controls over MCI to AD cases (Jiang et al, 2018). A significant association between fractal dimension and Montreal Cognitive Assessment (MoCA) could not be confirmed (Cabrera DeBuc et al, 2018).…”
Section: Outcomes Of Fractal Analysis In Studies On Neurodegenerativementioning
confidence: 90%
“…44 The peripheral retina may also hold clues-patients with AD appear to have both a higher baseline and an increase in peripheral hard drusen over two years of follow-up. 45 Anatomically, however, changes in the optic nerve and retinal nerve fiber layer would seem most plausible representatives of neurodegenerative disease. Early on, it was noted that red free retinal nerve fiber layer (RNFL) photographs reveal a higher proportion of defects in patients with AD, but this has not always been consistent, perhaps owing to the limited number of cases in many studies.…”
Section: Neurodegenerative Diseasementioning
confidence: 99%
“…A systematic review by Pellegrini et al [19] found over 110 publications on various initiatives where ML approaches have been employed to develop prediction models for cognitive impairment and AD using neuroimaging data. These research efforts are being extended to other data sources and domains such as linguistic analysis of text messages; speech analysis [20,21]; and also through the human eyes using retinal imaging [22] with promising results.…”
Section: Dementia Early Intervention Through Big Data and Ai In Lmicmentioning
confidence: 99%